2018
DOI: 10.1007/s10329-018-0679-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional decline of sweet taste sensitivity of colobine monkeys

Abstract: For many primates, sweet taste is palatable and is an indicator that the food contains carbohydrates, such as sugars and starches, as energy sources. However, we have found that Asian colobine monkeys (lutungs and langurs) have low sensitivity to various natural sugars. Sweet tastes are recognized when compounds bind to the sweet taste receptor TAS1R2/TAS1R3 in the oral cavity; accordingly, we conducted a functional assay using a heterologous expression system to evaluate the responses of Javan lutung (Trachyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Consistent with this result, our cell-based assays showed that the sweet taste receptors of the four insectivorous bats were not activated by any of the sugars tested in this study (Fig. 3), possibly due to mutations on critical functional domains of their receptors (37). Our subsequent assays on chimeric receptors supported this view and confirmed the functional importance of VFD domain of Tas1r2/Tas1r3 on sugar detection.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with this result, our cell-based assays showed that the sweet taste receptors of the four insectivorous bats were not activated by any of the sugars tested in this study (Fig. 3), possibly due to mutations on critical functional domains of their receptors (37). Our subsequent assays on chimeric receptors supported this view and confirmed the functional importance of VFD domain of Tas1r2/Tas1r3 on sugar detection.…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, we cannot directly infer that sweet taste perception mediated by the Tas1r2-Tas1r3 heterodimer is conserved in frugivorous and insectivorous bats because an intact coding sequence does not indicate an intact gene function and/or animal behavior (36,37). Therefore, we performed behavioral preference tests on R. leschenaultii (a congeneric species of R. aegyptiacus) and found strong behavioral preference toward natural sugars (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the genomic and proteomic information available indicates that the sweet taste receptor T1R2/T1R3 is widely distributed in all kingdoms of mammalia including primates ( Hellekant and Danilova, 1996 ; Li et al, 2009 ). To date, the T1R2s/T1R3s of primate species humans, squirrel monkeys and asian colobine monkeys have been characterized with the cell-based signal assays, indicating their functional differentiation ( Liu et al, 2011 ; Nishi et al, 2018 ). Furthermore, many behavioral and gustatory responses tests have shown diverse sweet taste preferences in primates, suggesting a high degree of functional flexibility ( Hellekant et al, 1981 ; Dieter et al, 1992 ; Hellekant et al, 1993 ; Hellekant and Danilova, 1996 ; Danilova et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%